Desain Asesmen Pembelajaran Proyek Berbasis STEAM Pada Implementasi Kurikulum Merdeka - Amsal Alhayat; Riche Cynthia J. (Postgraduate, University of Mataram, 2024)
This study aims to develop a learning assessment design with STEAM-based projects for implementing the Kurikulum Merdeka in junior high schools, focusing on the topic of environmental pollution. The Design-Based Research (DBR) approach was used, comprising three stages: analysis and exploration, design and construction, and evaluation and reflection. The assessment design was validated by three experts and tested with 35 students and a science teacher at a junior high school in Pontianak. Results from the analysis and exploration phase revealed that teachers needed a comprehensive assessment method to evaluate 21st-century skills. In the design phase, the developed assessment included project matrices and rubrics, receiving a validation score of 85.45%, indicating high validity. In the trial phase, teachers found the assessment design easy to use and effective in evaluating students' understanding of science and scientific processes. The design also identified students’ problem-solving and creative thinking skills. The findings suggest that this assessment could be a useful tool for evaluating students’ 21st-century skills and offers potential for further research, particularly in large-scale trials to improve its quality.